Meta-analysis of Chromatin Programming by Steroid Receptors - Paakinaho, Ville (2019)
Transcription factors (TFs) must access chromatin to bind to their response elements and regulate gene expression. A widely accepted model proposes that only a special subset of TFs, pioneer factors, can associate with condensed chromatin and initiate chromatin opening. We previously reported that steroid receptors (SRs), not considered pioneer factors, can assist the binding of an archetypal pioneer, the forkhead box protein 1 (FOXA1), at a subset of receptor-activated enhancers. These findings have been challenged recently, with the suggestion that newly acquired data fully support the prevailing pioneer model. Here, we reexamine our results and confirm the original conclusions. We also analyze and discuss a number of available datasets relevant to chromatin penetration by SRs and find a general consensus supporting our original observations. Hence, we propose that chromatin opening at some sites can be initiated by SRs, with a parallel recruitment of factors often treated as having a unique pioneer function.